2019
DOI: 10.1029/2018jg004683
|View full text |Cite
|
Sign up to set email alerts
|

Factors Controlling Storage, Sources, and Diagenetic State of Organic Carbon in a Prograding Subaerial Delta: Wax Lake Delta, Louisiana

Abstract: Wax Lake Delta, southern Louisiana, is a coastal delta that formed following the dredging of a river channel in 1941 and is a field model for investigating the geomorphology, ecology, carbon dynamics, and carbon storage capacity in young prograding deltas. However, it is unknown how the transition from subaqueous to subaerial sediments affects the sources and quality of the sequestered carbon. We investigated these variations within the sediments of Wax Lake Delta using amino acid, lignin, and stable carbon is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 101 publications
0
12
0
Order By: Relevance
“…Lignin‐phenols from the northern samples were extracted and analyzed, along with other cupric oxide (CuO) oxidation products, from freeze‐dried soil using the cupric oxide method of Hedges and Ertel (), modified by Louchouarn et al () and reported in detail in Shields et al (). Briefly, enough soil for 3–5 mg of OC was oxidized in a modified gas chromatograph oven for 3 hr at 150 °C using reaction vessels that contained soil, a stainless‐steel ball bearing, cupric oxide (CuO) powder, ferrous ammonium sulfate hexahydrate, and N 2 ‐sparged 2 N NaOH.…”
Section: Methodsmentioning
confidence: 99%
“…Lignin‐phenols from the northern samples were extracted and analyzed, along with other cupric oxide (CuO) oxidation products, from freeze‐dried soil using the cupric oxide method of Hedges and Ertel (), modified by Louchouarn et al () and reported in detail in Shields et al (). Briefly, enough soil for 3–5 mg of OC was oxidized in a modified gas chromatograph oven for 3 hr at 150 °C using reaction vessels that contained soil, a stainless‐steel ball bearing, cupric oxide (CuO) powder, ferrous ammonium sulfate hexahydrate, and N 2 ‐sparged 2 N NaOH.…”
Section: Methodsmentioning
confidence: 99%
“…Most samples from the YRE region plot below the 0.4 mg C org m −2 line, which indicates a lower than normal C org content (0.4–1.0 mg C org m −2 ). The low C org /SA ratios (<0.4 mg C org m −2 ) observed in the YRE are comparable with those of C org sequestered in other river‐dominated margins that experience frequently remobilization and reoxygenation, such as the Amazon shelf, Pan‐Arctic shelf, and Bengal Fan (Bianchi et al, ; Goñi et al, ; Shields et al, ). Therefore, it is possible that the occurrence of low C org /SA ratios in sediments is a result of the insufficient sediment supply, a low SAR, the enhanced degradation associated with coarser deposits, and long oxygen exposure times in association with physical and/or biological reworking.…”
Section: Discussionmentioning
confidence: 53%
“…Relationships between sedimentary C org and (a) TN, and (b) modeled sedimentary particle surface area for all sediment samples collected from the YRE. Specific surface area (SA) for sediment samples was calculated using the method described in Mayer and Rossi () and Shields et al (). The ranges of C org –SA loading (0.4–1.0 mg C org m −2 ) commonly observed in river‐suspended material are shown (Blair & Aller, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations